Technical note on introducing a digital workflow for newborns with craniofacial anomalies based on intraoral scans - part II: 3D printed Tübingen palatal plate prototype for newborns with Robin sequence - A. B. Xepapadeas; C. Weise; K. Frank; S. Spintzyk; C. F. Poets; C. Wiechers; J. Arand; B. Koos (BMC, 2020)
Abstract Background Orthodontic treatment of newborns and infants with Robin-Sequence using the Tübingen Palatal Plate (TPP) is a complex procedure that could benefit from simplification through digitalization. The design of the velar extension (spur) and the palatal base determines the success of the treatment. Therefore, a prototype must be produced and inserted under endoscopic supervision in order to determine the appropriate shape, length and position of the spur. This technical note demonstrates a fully digital workflow for the design and manufacturing of a functional TPP prototype, based on an intraoral scan. This prototype can be altered and individualized digitally for each patient. After the shape and position of the spur have been optimized, the prototype is duplicated using a silicone mold. Then the definitive TPP is manufactured and inserted. We aim to present a workflow which facilitates the fitting procedure and does not require a conventional impression or a physical model to create the appliance. Methods As described in part I of this series, the intraoral scan is performed using the 3Shape TRIOS3 scanner and its corresponding acquisition software. The virtual model is rendered in the 3Shape ortho appliance designer and the base of the palatal plate is designed in the 3Shape dental designer. The palatal plate and the virtual model are then imported into Autodesk Meshmixer and a standardized spur is positioned and merged with the base. The TPP is exported in Standard Tessellation Language (STL) format and manufactured on a W2P Solflex 170 DLP printer using VOCO VPrint Splint material (MDR Class IIa). Results Based on an intraoral scan, the TPP prototype could be successfully manufactured and proved suitable for the patients' treatment. Conclusion The new digital workflow for the design of the TPP can been successfully implemented into daily clinical routine in our facility. Patients could be alleviated from having to undergo conventional impression procedures and fitting of the TPP could be facilitated by producing multiple functional prototypes for endoscopic evaluation. Through rapid prototyping, the expenditure of the fitting process was reduced, which makes the TPP therapy more efficient and accessible to a wider range of clinicians.